Coensino e Educação Física Escolar: perspectivas colaborativas para a inclusão de estudantes com deficiência - Gatti, Melina Radaelli (Universidade Federal de São Carlos, 2020)
The enrollment of students with disabilities in ordinary schools has increased steadily in recent years. From the perspective of inclusive education, school physical education has sought to ensure opportunities for effective participation for students with disabilities, however, the physical education teacher still faces many challenges. Among the various difficulties faced by this professional, the lack of support services for inclusion in his area stands out. As a consequence, most students with disabilities are attending classes, but are not effectively participating in activities related to this curricular component. Then there is an interest in investigating the co-teaching as a possibility of support service for the Physical Education teacher. Thus, the general objective of the study focuses on analyzing the possibilities and limitations of the co-teaching as a support service to promote the inclusion of students with disabilities in the context of school Physical Education, from a collaborative perspective. Specifically, it is intended: to describe and analyze the forms of intervention with the protagonist agents (Physical Education Teacher, student with disabilities and their peers) involved in this process; to identify the different types of support provided by the collaborating teacher, a specialist in Special Education (researcher) in school Physical Education classes; and to evaluate co-teaching based intervention from the perspective of Physical Education teachers. This is a study with a qualitative approach, characterized as collaborative research. Data collection was carried out in two municipal schools in a small city in the interior of the state of São Paulo, selected for convenience criteria. The participants were three Physical Education teachers, their respective classes and a collaborating teacher specialized in school Physical Education. The role of collaborating teacher was played by the researcher, a specialist in Physical Education at School and Special Education. As instruments of data collection, semi-structured interviews and systematic observation were used. The treatment of the data was based on thematic analysis and the results were presented in three parts: step I describes the intervention with each of the participants (case 1, case 2 and case 3), highlighting the various phases of collaborative action (communication, co-planning, codocence, co-evaluation); stage II addresses the support modalities of the co-teaching in Physical Education classes; stage III covers the co-teaching from the perspective of the participating teachers, according to the following thematic categories: 1. inclusion in Physical Education classes; 2. Interpersonal relationships, a) teacher x student with disabilities, b) student with disabilities x class; 3. collaboration / co-teaching. It is concluded that the co-teaching, as a teaching model and support service, provided different supports favorable to the inclusion process of students with disabilities; it was possible to apply the co-teaching models found in the literature, verifying the effectiveness of this collaborative intervention in the context of school Physical Education.
Co-teaching and School Physical Education: collaborative perspectives for the inclusion of students with disabilities
Keywords: Educação Física Escolar; Coensino; Educação Especial; Educação Inclusiva; Deficiência; School Physical Education; Co-teaching; Special Education; Education Inclusive; Disabilities; CIENCIAS HUMANAS::EDUCACAO::ENSINO-APRENDIZAGEM